Integrating genome-wide association study and expression quantitative trait locus study identifies multiple genes and gene sets associated with schizophrenia - Zhao, Yan; He, Awen; Zhu, Feng; Ding, Miao; Hao, Jingcan; Fan, Qianrui; Li, Ping; Liu, Li; Du, Yanan; Liang, Xiao; Guo, Xiong; Zhang, Feng; et al. (Progress in neuro-psychopharmacology & biological psychiatry, 2018)
Schizophrenia is a serious mental disease with high heritability. To better understand the genetic basis of schizophrenia, we conducted a large scale integrative analysis of genome-wide association study (GWAS) and expression quantitative trait loci (eQTLs) data. GWAS summary data was derived from a published GWAS of schizophrenia, containing 9394 schizophrenia patients and 12,462 healthy controls. The eQTLs dataset was obtained from an eQTLs meta-analysis of 5311 subjects, containing 923,021 cis-eQTLs for 14,329 genes and 4732 trans-eQTLs for 2612 genes. Genome-wide single gene expression association analysis was conducted by SMR software. The SMR analysis results were further subjected to gene set enrichment analysis (GSEA) to identify schizophrenia associated gene sets. SMR detected 49 genes significantly associated with schizophrenia. The top five significant genes were CRELD2 (p value=1.65×10−11), DIP2B (p value=3.94×10−11), ZDHHC18 (p value=1.52×10−10) and ZDHHC5 (p value=7.45×10−10), C11ORF75 (p value=3.70×10−9). GSEA identified 80 gene sets with p values <0.01. The top five significant gene sets were COWLING_MYCN_TARGETS (p value <0.001) and CHR16P11 (p value <0.001), ACTACCT_MIR196A_MIR196B (p value=0.002), CELLULAR_COMPONENT_DISASSEMBLY (p value=0.002) and GRAESSMANN_RESPONSE_TO_MC_AND_DOXORUBICIN_DN (p value=0.002). Our results provide useful information for revealing the genetic basis of schizophrenia. •The first large scale integrative study of GWAS and eQTLs was conducted for schizophrenia.•SMR analysis identified 49 significant genes, whose expression levels were related to schizophrenia.•Enrichment analysis detected 80 gene sets significantly associated with schizophrenia.•Our results expand the understanding of the genetic mechanism of schizophrenia.